OPTIMALISASI STRATEGI PEMASARAN UNTUK MENINGKATKAN PENDAPATAN PADA UMKM SATE BULAYAK DI DESA LEMBUAK KECAMATAN NARMADA KABUPATEN LOMBOK BARAT - Taufikurrahman, Muhammad; Hidayati, Siti Aisyah; Izzati, Nurul Fardatul; Ramadhan, Wulan Suci; Juliana, Nana; Fahreza, Faiz Ridho; Halimatussakdiah; Nurlailah; Putra, Gusti Ngurah Eka; Syarif, Lalu Rosihan; Putri, Baiq Adisty Tahira (Jurnal Wicara, 2024)
Community Service Program (KKN) are a form of community service activities carried out by universities. In KKN carried out in Lembuak Village, Narmada Distric, West Lombok Regency, a group of Mataram University students and lectures carried out various activities with the main target being mapping and developing village potensial. The aim of implementing this KKN is to help the community in increasing income at bulayak satay UMKM in Lembuak Village, Narmada Distric, West Lombok Regency. There are several activity methods carried out, namely creating a village website and packaging innovation for bulayak satay products. The result of this activity is the availability of a website that can be used by UMKM in Lembuak Village to market bulayak satay and innovation in packaging bulayak satay so that it can be marketed outside the area. Apart from that, the KKN group is also involved in various other activities, namely posyandu, teaching and learning at PAUD, and mutual cooperation. The result of the activities above show that this KKN activity has been able to answer several problems in Lembuak Village related to increasing income for bulayak satay UMKM in Lembuak Village, Narmada District, West Lombok Regency.